Remote effect of tropical South Atlantic variability on the Pacific–Japan pattern - Wenwen Yang; Xichen Li; Lin Wang; Yurong Hou; Yonghao Wang; Yujie Miao; Weihan Ma (Climate Dynamics, 2025)

Interdecadal variability of winter and spring Eurasian snow depth and its impact on Eastern China precipitation - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Yumeng Liu; Hanhui Zhu (Climate Dynamics, 2024)
Empirical orthogonal function (EOF) and correlation analyses were employed to investigate the winter and spring snow depth in Eurasia and its relationship with Eastern China precipitation based on the observed and reanalyzed data from 1980 to 2016. The results show that the winter and spring snow cover in Eurasia not only highlights a decreasing trend due to global warming (the first EOF mode, its variance accounted for 24.4% and 22.6% of the total variance) but also exhibits notable interdecadal variation (the second EOF mode, its variance accounted for 10.2% and 11.5% of the total variance). The second EOF mode of winter snow depth in Eurasia is characterized by a west-east dipole pattern. It was observed that the spatial correlation pattern between the EOF2 of Eurasian snow depth and summer precipitation in China closely resembles the meridional quadrupole structure of the third EOF mode of summer precipitation in China. This pattern is characterized by excessive rainfall in Northeast China and the lower-middle reaches of the Yangtze River, and less rainfall over the Yellow River basin and southern China. The EOF mode of spring snow depth not only reflects the declining trend but also regulates precipitation in Eastern China. The possible mechanisms by which snow depth causes changes in soil moisture and subsequently affects atmospheric circulation are then explored from the perspective of the hydrological effects of snow cover. Decreased (Increased) snow depth in Eurasia during the winter and spring directly leads to diminished (increased) soil moisture while increasing (decreasing) net radiation and sensible heat flux at the surface. The meridional distribution of surface temperature also exhibits a dipole pattern, leading to enhanced subtropical westerly jet in the upper troposphere. The Eurasian snow cover anomalies pattern triggered an anomalous mid-latitude Eurasian wave train, which strengthened significantly in the Western Siberian Plain. It then splits into two branches, one continuing to propagate eastward at high latitudes and the other shifting towards East Asia, thereby impacting precipitation in Eastern China. This work indicates that the second EOF mode of Eurasian snow cover can impact the precipitation variability in Eastern China during the same period and in summer on an interdecadal scale.

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Impacts of physical parameterization scheme of snow and soil properties over the Tibetan Plateau on the simulation of summer rainfall in China - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Shiwen Wang; Yumeng Liu (Climate Dynamics, 2024)
Accurate representation of soil and snow state variables in the land surface model is crucial for good simulation results. In order to investigate the potential impacts of the overestimated snow cover over the Tibetan Plateau (TP) on precipitation over China, we designed comparative experiments over TP with and without updated soil texture data, soil hydrological parameters, and the fresh snow density scheme to address this issue with the Weather Research and Forecasting Model (WRF). The results show that snow cover fraction (SCF) and surface albedo in winter on the TP were overestimated in the WRF control experiment (CTL), with albedo bias exceeding 0.4 in the western TP. The SCF in the WRF improved experiment (WRFIM) is about 8% lower than that of the CTL, and the bias is decreased to 0.2–0.3 in the interior of the TP. The thermal and dynamic effects of the TP in winter have a significant impact on the weather and climate of East Asia during summer. Thus, the simulated summer rainfall bias is significantly reduced by WRFIM in North China, and the mid-lower reaches of the Yangtze River, along with the spatial correlation coefficient between the observed-based and WRF-simulated rainfall increased from 0.76 in CTL to 0.88 in WRFIM. The WRFIM-simulated reductions in snow cover and albedo cause a decrease in upward shortwave radiation and eventually increase net surface radiation. The horizontal temperature gradient of the atmosphere is increased in the WRFIM compared to the CTL, and the increased temperature in the lower and middle layers accommodates more water vapor, which is not conducive to precipitation formation. Correspondingly, the Western Pacific Subtropical High at 500 hPa in the middle troposphere weakened. The low-level anticyclonic circulation at 850 hPa also weakened to the east, affecting water vapor transport in eastern China. It leads to a decrease in the water vapor transported northward by southeasterly from the western Pacific Ocean and a decrease in the water vapor flux reaching North China. This work indicates that accurate characterization of soil properties and snow cover on the TP is crucial for improving the simulation bias of summer rainfall in China.

Mechanisms of persistent heavy rainfall related to 10–30‑day oscillation during pre- and post-monsoon-onset periods in the first rainy season over South China - Chunhui Li; Jing Wang; Dejun Gu; Ailan Lin; Bin Zheng; Dongdong Peng; Jinhai He (Climate Dynamics, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

The dynamics of the equatorial Atlantic upwelling seasonal cycle under global warming and its potential impact on Pacific ENSO - Li-Chiao Wang; Thi Lan Dao; Yong-Fu Lin; Jia-Yuh Yu (Climate Dynamics, 2023)

Enhanced soil respiration, vegetation and monsoon precipitation at Lantian, East Asia during Pliocene warmth - Kexin Wang; Huayu Lu; Carmala N. Garzione; Lin Zhao; Chenghong Liang; Shuyue Li; Daniel O. Breecker; Fang Lei; Hongyan Zhang (Climate Dynamics, 2022)

Added value of kilometer-scale modeling over the third pole region: a CORDEX-CPTP pilot study - Xu Zhou; Kun Yang; Lin Ouyang; Yan Wang; Yaozhi Jiang; Xin Li; Deliang Chen; Andreas Prein (Climate Dynamics, 2021)

Effects of high-frequency surface wind on the intraseasonal SST associated with the Madden-Julian oscillation - Yingxia Gao; Pang-Chi Hsu; Lin Chen; Lu Wang; Tim Li (Climate Dynamics, 2020)

A new DRP-4DVar-based coupled data assimilation system for decadal predictions using a fast online localization technique - Yujun He; Bin Wang; Wenyu Huang; Shiming Xu; Yong Wang; Li Liu; Lijuan Li; Juanjuan Liu; Yongqiang Yu; Yanluan Lin; Xiaomeng Huang; Yiran Peng (Climate Dynamics, 2020)

Improving prediction of two ENSO types using a multi-model ensemble based on stepwise pattern projection model - Lin Wang; Hong-Li Ren; Jieshun Zhu; Bohua Huang (Climate Dynamics, 2020)
This study focuses on improving prediction of the two types of ENSO by combining multi-model ensemble (MME) with a statistical error correction method that is based on a stepwise pattern projection and applied to all models before doing the MME. We evaluate such a combinational approach using five dynamical model datasets from the North American Multi-model Ensemble (NMME) project for the period of 1982–2010. The prediction skills of the proposed MME show an improvement over most tropical Pacific regions. With regard to the two ENSO types, improvements in prediction skills of the proposed MME are particularly evident for the Niño indices for short lead time. The differences between the Eastern Pacific and Central Pacific ENSO types are more pronounced in the corrected forecasts compared with the uncorrected ones. The zonal center position of sea surface temperature anomalies for the corrected MME is closer to the observed than that for the uncorrected MME. The results indicate that reducing prediction errors of each model member by a good correction method before applying the MME method can provide an effective way for empirically improving forecasts of the two ENSO types.

Contribution of SST change to multidecadal global and continental surface air temperature trends between 1910 and 2013 - Yidan Xu; Jianping Li; Cheng Sun; Xiaopei Lin; Hailong Liu; Lanning Wang; Yishuang Liang; Qiuyun Wang; Yazhou Zhang; Zhaolu Hou; Fuchang Wang (Climate Dynamics, 2020)
The global mean surface air temperature (GMST) shows multidecadal variability over the period of 1910–2013, with an increasing trend. This study quantifies the contribution of hemispheric surface air temperature (SAT) variations and individual ocean sea surface temperature (SST) changes to the GMST multidecadal variability for 1910–2013. At the hemispheric scale, both the Goddard Institute for Space Studies (GISS) observations and the Community Earth System Model (CESM) Community Atmosphere Model 5.3 (CAM5.3) simulation indicate that the Northern Hemisphere (NH) favors the GMST multidecadal trend during periods of accelerated warming (1910–1945, 1975–1998) and cooling (1940–1975, 2001–2013), whereas the Southern Hemisphere (SH) slows the intensity of both warming and cooling processes. The contribution of the NH SAT variation to the GMST multidecadal trend is higher than that of the SH. We conduct six experiments with different ocean SST forcing, and find that all the oceans make positive contributions to the GMST multidecadal trend during rapid warming periods. However, only the Indian, North Atlantic, and western Pacific oceans make positive contributions to the GMST multidecadal trend between 1940 and 1975, whereas only the tropical Pacific and the North Pacific SSTs contribute to the GMST multidecadal trend between 2001 and 2013. The North Atlantic and western Pacific oceans have important impacts on modulating the GMST multidecadal trend across the entire 20th century. Each ocean makes different contributions to the SAT multidecadal trend of different continents during different periods.

Dynamical impact of parameterized turbulent orographic form drag on the simulation of winter precipitation over the western Tibetan Plateau - Xu Zhou; Kun Yang; Anton Beljaars; Huidong Li; Changgui Lin; Bo Huang; Yan Wang (Climate Dynamics, 2019)

Drivers of reduced ENSO variability in mid-Holocene in a coupled model - Lin Chen; Lu Wang; Tim Li; Jian Liu (Climate Dynamics, 2019)

Declining diurnal temperature range in the North China Plain related to environmental changes - Weitao Xue; Jianping Guo; Yong Zhang; Shunwu Zhou; Yuan Wang; Yucong Miao; Lin Liu; Hui Xu; Jian Li; Dandan Chen; Huan Liu (Climate Dynamics, 2019)

Modulation of the Madden–Julian oscillation on the energetics of wintertime synoptic-scale disturbances - Lu Wang; Tim Li; Lin Chen (Climate Dynamics, 2019)

The dominant role of the atmospheric component of coupled models in ENSO amplitude simulations - Yanli Tang; Lijuan Li; Bin Wang; Pengfei Lin; Lin Chen; Feng Xie; Wenjie Dong; Kun Xia (Climate Dynamics, 2019)

A possible mechanism for the occurrence of wintertime extreme precipitation events over South China - Wenyu Huang; Zifan Yang; Xinsheng He; Daiyu Lin; Bin Wang; Jonathon S. Wright; Ruyan Chen; Wenqian Ma; Feifei Li (Climate Dynamics, 2019)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

Modulation of the MJO intensity over the equatorial western Pacific by two types of El Niño - Lu Wang; Tim Li; Lin Chen; Swadhin K. Behera; Tomoe Nasuno (Climate Dynamics, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

Dynamically-downscaled projections of changes in temperature extremes over China - Junhong Guo; Guohe Huang; Xiuquan Wang; Yongping Li; Qianguo Lin (Climate Dynamics, 2018)